Impact of flooding on the variability of chemical and microbiological state of chestnut soils of Western Kazakhstan Region - Nagiyeva, Aliya; Ongayev, Marat; Japarov, Rashit; Ayupov, Yergali; Denizbayev, Serik (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of the research was to investigate changes in the soil microbiome and soil chemicals due to the flooding of agricultural areas, as well as to determine the strength of the relationship between these soil indicators. Deliberate flooding is a reliable way to procure cheap and highly nutritious fodder. More than 400 thousand hectares of flooded lands in the republic are concentrated in Western Kazakhstan, where the research was conducted. The research methodology included, along with an agrochemical study of soil fertility, a metagenomic analysis using high-throughput sequencing. All basic soil parameters of the flooded site were compared with the non-irrigated site, which allowed for the identification of the main changes and processes affecting soil fertility by comparison. The results of the study showed that annual flooding led to an increase in the main soil indicator humus, on average by 0.10–0.28% in genetic horizons in comparison with the non-flooded site. Flooding reduced the alkalinity of the soil solution to 7.7 pH, as well as the degree of salinity to weak. Representatives of bacterial communities Proteobacteria, Actinobacteria, Firmicutes, NA, and Verrucomicrobia dominated in the soil samples of the studied plots, while representatives of Acidobacteria, Bacteroidetes, Planctomycetes, Caldithrix, Chloroflexi, and Tenericutes appeared in smaller shares. A high degree of correlation was found only between the chemical parameters of the soil, pH and the sum of salts, with representatives of the bacterial phylum Verrucomicrobia, NA, Acidobacteria, and Caldithrix. Analysis of the correlation field showed a negative type of relationship between the above indicators.